2010
DOI: 10.1111/j.1469-7998.2010.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary stay at various environmental humidities affects attachment ability of Colorado potato beetles Leptinotarsa decemlineata (Coleoptera, Chrysomelidae)

Abstract: In a natural environment, insects live in different microhabitats varying in their humidity. Because insect adhesive mechanism at least partly relies on the capillary force, it is natural to assume that environmental humidity may considerably influence insect attachment. However, this aspect has been neglected in the literature so far. We present the first experimental study demonstrating the influence of the exposure to moist surfaces on the attachment of Colorado potato beetles Leptinotarsa decemlineata. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This argument was recently used as an explanation for humidity-enhanced adhesion of gecko setae [19]. In insects it has been reported that resting in a humid environment positively influences attachment forces [29]. This could be owing to the hydration of setae.…”
Section: Discussion (A) Humidity Optimum For Dry Adhesionmentioning
confidence: 98%
“…This argument was recently used as an explanation for humidity-enhanced adhesion of gecko setae [19]. In insects it has been reported that resting in a humid environment positively influences attachment forces [29]. This could be owing to the hydration of setae.…”
Section: Discussion (A) Humidity Optimum For Dry Adhesionmentioning
confidence: 98%
“…The results of this study clearly indicate that ants, and probably other insects with smooth tarsal pads, are unable to do this, as there are only fine wrinkles on the tarsal pads (see [49] and [50] for images of cockroach and stick insect smooth pads, respectively). Physical limitations of the smooth pad are probably heightened on flooded surfaces, similar to the fibrillar pads of beetles and spiders [51][52][53], where adhesion-enhancing capillary effects are eliminated due to thick water layers that build up in high humidity, or when ant tarsi encounter standing water from rain. Resolving the physical mechanisms for these patterns was beyond the scope of this study but is a potentially fruitful direction for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Voigt et al [48] observed significantly higher forces generated by beetles ( Leptinotarsa decemlineata ) on a dry surface, which were kept prior the experiment under humid conditions if compared to beetles kept prior the experiment under dry conditions. In the present study we observed a distinct difference between both types of experiments (Experiment 1 and 2).…”
Section: Discussionmentioning
confidence: 99%